A Literature Analysis of “Kering” By Iwan Simatupang - Rosmani Sianipar (Universitas Pasundan, 2022)
Iwan Simatupang the great writer was born on January 18, 1928. Lots of his works have been translated into various languages, while the demand for reprints continues to increase. Iwan Simatupang's